Pengaruh Penggunaan Quick Response Code Indonesian Standard (QRIS) Oleh UMKM Terhadap Pendapatan Usaha - Fahrudin Fahrudin; Putri Lailatul Isnaini (Fakultas Ekonomi Universitas Andalas, 2023)
QRIS is an aggregation of QR codes from several types of Penyelenggara Jasa Sistem Pembayaran (PJSP) using only one QR code (Bank Indonesia, 2020). QRIS is here to facilitate cashless payment transactions. But unfortunately, in using QRIS there are MDR and Settlement costs that are charged to UMKM so that it has the potential to reduce UMKM income. This study aims to test and analyze how the influence of the use of QRIS through the PJSP DANA application by UMKM has on business income in Kraksaan District. The method used is quantitative with simple linear regression analysis, partial test (t test), and test the coefficient of determination (R2 test). Data collection through questionnaires, observation, and literature study. Questionnaires were distributed to 50 UMKM that had used QRIS through PJSP DANA according to the data recorded on the DANA Application. Based on the results of the study, it shows that the use of QRIS through the provider of the DANA application payment system service has a positive effect on business income in Kraksaan District.